Achieving dispersed fine soft Bi particles and grain refinement in a hypermonotectic Al–Bi alloy by severe plastic deformation and annealing. (October 2018) - Zha, Min; Yu, Zhi-Yuan; Qian, Feng; Wang, Hui-Yuan; Li, Yan-Jun; Mathiesen, Ragnvald H.; Roven, Hans J.
Abstract: The present work revealed that equal-channel angular pressing (ECAP) deformation combined with appropriate annealing could represent as an efficient route to modify immiscible as-cast microstructure of a monotectic Al–8Bi alloy by a complete redistribution of immiscible Bi particles and grain refinement of alloy matrix. Especially, we found that the mean size of Bi particles in the 4-pass ECAPed Al–8Bi sample decreases after annealing at 200 °C for 8 h, due to inverse coarsening driven by the reduction of elastic energy and interfacial energy induced by morphology change and spatial distribution of Bi particles. Graphical abstract: Unlabelled Image